Pembuatan Modul Ajar Matematika Berbasis PjBL Berbantuan Teknologi Artificial Intelligence ChatGPT pada MGMP Matematika SMP - Wahyudi, Dahlan; Afandi, Ahmad; Syam Tonra, Winda; Angkotasan, Nurma (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
The purpose of the community service program (PKM) is to train teachers in making math teaching modules based on project-based learning (PjBL) using the help of Artificial Intelligence (AI) ChatGPT. This way, math teachers in Ternate can create their own teaching modules before applying the PjBL model in the classroom. The methods used in this program are: 1) Presentation and Discussion Method : This involves explaining the goals and benefits of the activity, giving a brief explanation about the Teaching Module and AI technology, including the AI feature ChatGPT, 2) Demonstration and Training Method : This explains the steps to create a math teaching module based on PjBL with the help of AI ChatGPT. In the training, the pretest results showed that many teachers still could not make PjBL math modules. They were confused about what projects could be done in class, especially for difficult material. However, after the training on using AI ChatGPT to create teaching modules, the teachers were finally able to make PjBL modules for all math topics. At the end of the training, the teachers were given an evaluation. The result was 98.39%, which means the training received a positive response and was useful for them. In conclusion, the PKM activity showed that math teachers in Ternate can now create their own teaching modules using AI ChatGPT.